Maize-based intercropping systems and determinants of practices: implications for the adoption of a push-pull technology for insect pest management in the Republic of Benin - Gavoedo, Dieudonne M.; Loko, Yêyinou Laura Estelle; Toffa, Joelle; Dassou, Anicet; Djegbe, Innocent; Tossou, Eric; Yadouleton, Anges (Frontiers in Horticulture, 2026)
IntroductionMaize (Zea mays L.) is the most commonly grown cereal crop in Benin and is a staple for millions of people. However, its production is hampered by insect pests such as the fall armyworm (Spodoptera frugiperda J. E. Smith), which causes substantial yield losses. Chemical pest control has demonstrated several limitations, leading to the promotion of ecological approaches such as pushpull technology, which deters insect pests through strategic intercropping. Promoting this technology in Benin requires an understanding of the maize-based intercropping systems developed by Beninese farmers across different agroecological zones and ethnic groups, as well as their perception of crop associations. It is also crucial to identify the factors that have an impact on the adoption of a maize-based intercropping system.MethodsTo access this technology in Benin, 438 farmers from 60 villages located in seven agroecological zones, belonging to eight sociolinguistic groups, were interviewed using participatory methods.Results and DiscussionAccording to the findings, crop association was practiced by 70.56% of surveyed the farmers in their maize fields, and four distinct crop association types and systems were documented. Farmers listed six constraints that hinder the use of maize-based intercropping systems, with field maintenance difficulty (60.54% of responses) being the most important. Cultural prohibitions or taboos (21.67% of responses) regarding intercropping systems such as maize and common beans were recorded in the study area. The practices and types of crop associations vary according to ethnic groups and agroecological zones. The push-pull method should be implemented in Benin by targeting Yoa-Lokpa and Fon ethnic groups and agroecological zones 4 and 8. For mass adoption of the push-pull technology by Beninese farmers, it is necessary to implement participatory methods such as farmer field schools or field days and target farmers with extensive agricultural experience.